Phytic acid content may affect starch digestibility and glycemic index value of rice (Oryza sativa L.) - Kumar, Awadhesh; Sahu, Chandrasekhar; Panda, Puja A; Biswal, Monalisa; Sah, Rameswar P; Lal, Milan K; Baig, Mirza J; Swain, Padmini; Behera, Lambodar; Chattopadhyay, Krishnendu; Sharma, Srigopal (Journal of the science of food and agriculture, 2020)
BACKGROUND Phytic acid (PA) is an anti‐nutrient present in cereals and pulses. It is known to reduce mineral bioavailability and inhibit starch‐digesting α‐amylase (which requires calcium for activity) in the human gut. In principle, the greater the amount of PA, the lower is the rate of starch hydrolysis. It is reflected in the lower glycemic index (GI) value of food. People leading sedentary lifestyles and consuming rice as a staple food are likely to develop type 2 diabetes. Hence, this study was planned to understand how PA content of different rice varieties affects the GI. RESULTS Rice Khira and Mugai which had very low PA (0.30 and 0.36 g kg−1, respectively) had higher GI values and α‐amylase activity, while Nua Dhusara and the pigmented rice Manipuri black rice (MBR) which had high PA (2.13 and 2.98 g kg−1, respectively) showed low α‐amylase activity and GI values. This relationship was statistically significant, though a weak relationship was found for the pigmented rice. Expression levels of MIPSI, IPKI and GBSSI markedly increased in the middle stage of grain development in all of the six genotypes having contrasting PA and GI. Maximum expression of MIPSI and IPKI was observed in Nua Dhusara and MBR (which had high PA) while that of GBSSI was observed in Khira and Mugai (with higher GI) at middle stage showing a negative correlation between PA and GI. CONCLUSIONS The data indicate that high PA content in rice might have an adverse effect on starch digestibility resulting in slower starch digestion in the human gut and consequently low glycemic response. © 2019 Society of Chemical Industry